Enhancing Tourism Through Smart Tourism: A Comparison of Aceh and Bali - Mikyal Munawwarah; Nabilla Febridha; Hafiz Himawan (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
In the age of digitalisation, tourism must adapt quickly to changing trends and technology. Smart tourism is key to improving service quality and the local economy. However, Aceh still faces challenges of inadequate infrastructure, weak use of digital platforms, and tourism promotion. This research aims to provide recommendations to the Aceh government in improving Aceh tourism through the implementation of smart tourism and Aceh can adopt Bali tourism which has implemented Smart Tourism and Bali's infrastructure is adequate, both for the public, and for disabilities. Bali has also used applications or websites to facilitate tourists visiting Bali. By adopting this digital strategy, Aceh can increase its tourism competitiveness and local revenue. In increasing the number of local and foreign tourist visits, Aceh can improve three things in the tourism sector, namely improving infrastructure, revamping and developing digital platforms, and increasing promotion through digital platforms